Genome sequence of Novosphingobium malaysiense strain MUSC 273T, novel alpha-proteobacterium isolated from intertidal soil - Hooi-Leng Ser; Wai-Fong Yin; Kok-Gan Chan; Nurul-Syakima Ab Mutalib; Learn-Han Lee (Progress in Microbes and Molecular Biology)
Novosphingobium malaysiense strain MUSC 273T is a recently identified Gram-negative, aerobic alpha-proteobacterium. The strain was isolated from intertidal soil with strong catalase activity. The genome sequence comprises 5,027,021 bp, with 50 tRNA and 3 rRNA genes. Further analysis identified presence of secondary metabolite gene clusters within genome of MUSC 273T. Knowledge of the genomic features of the strain may allow further biotechnological exploitation, particularly for production of secondary metabolites as well as production of industrially important enzymes